Work models as an element of the employer brand in the Polish labour market - Gryko, Arkadiusz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2024)
The development of digital technologies and the experience of pandemics have transformed traditional work models. For some employees, the ability to work from outside the organization’s headquarters has become a condition for employment. To meet these expectations, many employers offer their employees the opportunity to provide work both on-site and in hybrid or remote form. This is reflected in the content of job advertisements. This article attempts to indicate to what extent entrepreneurs use the freedom of employees to choose the work model to build an employer brand to attract candidates. A desk research analysis was conducted comparing secondary survey data on employees’ preferred work models and data on the number of job advertisements that offer job candidates the opportunity to choose the form of work. A linear correlation was conducted to assess the potential relationship between these variables. The article does not limit itself to presenting the study’s results but also attempts to indicate the causes and scale of the phenomenon. Due to the exploratory nature of the publication, the research hypotheses set were subjected to preliminary verification, indicating the need to continue and deepen the research.